The basic reproduction quotient (Q0) as a potential spatial predictor of the seasonality of ovine haemonchosis - Muhammad-Bashir Bolajoko; Hannah Rose; Vincenzo Musella; Antonio Bosco; Laura Rinaldi; Jan van Dijk; Giuseppe Cringoli; Eric R. Morgan (Geospatial Health, 2015)
Haemonchus contortus is a gastrointestinal nematode parasite of small ruminants, which feeds on blood and causes significant disease and production loss in sheep and goats, especially in warmer parts of the world. The life cycle includes free-living immature stages, which are subject to climatic influences on development, survival and availability, and this species therefore exhibits spatio-temporal heterogeneity in its infection pressure based on the prevailing climate. Models that better explain this heterogeneity could predict future epidemiological changes. The basic reproduction quotient (Q0) was used as a simple process-based model to predict climate-driven changes in the potential transmission of H. contortus across widely different geo-climatic zones, and showed good agreement with the observed frequency of this species in the gastrointestinal nematode fauna of sheep (r = 0.81, P <0.01). Averaged monthly Q0 output was further used within a geographical information system (GIS) to produce preliminary haemonchosis risk maps for the United Kingdom (UK) over a four-year historical span and under future climate change scenarios. Prolonged transmission seasons throughout the UK are predicted, especially in the south although with restricted transmission in peak summer due to rainfall limitation. Additional predictive ability might be achieved if information such as host density and distribution, grazing pattern and edaphic conditions were included as risk layers in the GIS-based risk map. However, validation of such risk maps presents a significant challenge, with georeferenced observed data of sufficient spatial and temporal resolution rarely available and difficult to obtain.